ANALISIS AKTIVITAS TOKSISITAS BEBERAPA MINYAK ATSIRI DENGAN METODE BRINE SHRIMP LETHALITY TEST - Utami, Marsah Rahmawati; Ardiyanti, Yusi (Journal of Holistic and Health Sciences (Jurnal Ilmu Holistik dan Kesehatan), 2019)
Background: Essential oils are commonly used as raw materials for fragrance oils, medicines and cosmetics. In the pharmaceutical field, essential oils are used as antibacterial, anti-pain and anti-infection. This pharmacological effect is related to secondary metabolites contained in the essential oil. The effectiveness of the active components of secondary metabolites as a drug can be determined by toxicity analysis as a preliminary test. Toxicity analysis that is commonly used is the Brine Shrimp Lethality Test (BSLT). This test illustrates the level of toxicity of extracts against Artemia salina larvae. The results of this test can be used as a preliminary test to identify broader plant bioactivity. Objective: The aim of this study was to analyze the toxicity activities of basil leaf essential oils, galangal rhizome and red betel leaf and their secondary metabolite content. Method: Essential oils were isolated by the steam distillation method, their toxicity activity was tested by the BSLT method, and the contents of the chemical compounds were analyzed by GC-MS. Conclusion: Brine Shrimp Lethality Test results showed that the essential oils of the leaves of the kemanggi, galangal rhizome, and red betel have a level of toxicity with LC50 respectively 57.21 ppm, 110.01 ppm, 360.51 ppm. Based on the results of GC-MS analysis, the main components of the kemanggi leaf essentialoil are lemonal and beta citral, the main components of galangal rhizome essential oil are 2,6-dimethylphenyl borate an 1,8-cineol, while the main components of the red betel essential oil are sabinena and beta mircena.